Gender dynamics in the cattle sector in Central America: A literature review - Gallina, Ambra (2016)
Cattle production is an important economic activity throughout Central America. Dairy production, in particular, is an important activity for many smallholder farmers in Costa Rica and across the Central America region. Women’s role in cattle production tends to be poorly valued and recognized, however. This literature review summarizes the scant research published about gender in the cattle sector in Central America, including the findings that (1) women lack access to and control over productive resources in the cattle sector and (2) extension services and training do not focus on women, likely because women’s contributions are undervalued. The paper then describes a successful project in Nicaragua and recommends areas for research.